(untitled) (Development Service Industry Management, 2025)
Under conditions of high turbulence, digital transformation and global competition, Ukrainian enterprises are compelled to seek integrated mechanisms capable of supporting operational resilience while ensuring strategic agility. Controlling emerges as a key instrument that combines financial and non-financial metrics, thereby supporting evidence-based managerial decisions. Despite the acknowledged effectiveness of controlling in global practice, its implementation in Ukraine remains fragmented: qualified personnel are scarce, digital systems are only partially integrated, and a results-measurement culture is still taking shape. These factors diminish business adaptability in times of crisis and rapid change. This research seeks to systematise the stages of controlling evolution, outline current development trends, and identify barriers to integrating controlling systems into the management of Ukrainian enterprises. The article analyses: (1) the genesis of controlling from financial control to digital analytics platforms; (2) the role of ERP, BI, and Big Data technologies in creating a unified information environment; (3) the integration of ESG indicators into the strategic controlling system; and (4) organisational and HR challenges of implementing controlling in Ukraine. A phased model for the digital transformation of the controlling function is proposed, encompassing staff competence development, data standardisation, and the introduction of scenario planning. Controlling has proven its ability to enhance transparency and managerial effectiveness, yet its potential in Ukraine is not fully realised. Overcoming existing barriers will require a combination of state support for digitalisation, corporate training programmes, and the deployment of adaptive analytical tools that transform controlling from an “island” of reporting into the core of strategic enterprise development.